Nencki Affective Picture System: Cross-Cultural Study in Europe and Iran - Riegel, Monika; Moslehi, Abnoos; Michałowski, Jarosław M.; Żurawski, Łukasz; Horvat, Marko; Wypych, Marek; Jednoróg, Katarzyna; Marchewka, Artur (Frontiers in Psychology, 2017)
Although emotions have been assumed conventionally to be universal, recent studies have suggested that various aspects of emotions may be mediated by cultural background. The purpose of our research was to test these contradictory views, in the case of the subjective evaluation of visual affective stimuli. We also sought to validate the recently introduced Nencki Affective Picture System (NAPS) database on a different cultural group. Since there has been, to date, no attempt to compare the emotions of a culturally distinct sample of Iranians with those of Europeans, subjective ratings were collected from 40 Iranians and 39 Europeans. Each cultural group was asked separately to provide normative affective ratings and classify pictures according to discrete emotions. The results were analyzed to identify cultural differences in the ratings of individual images. One hundred and seventy NAPS pictures were rated with regard to the intensity of the basic emotions (happiness, sadness, fear, surprise, anger, disgust) they elicited, as well as in terms of affective dimensions (valence and arousal). Contrary to previous studies using the International Affective Picture System (IAPS), our results for Europeans and Iranians show that neither the ratings for affective dimensions nor for basic emotions differed across cultural groups. In both cultural groups, the relationship between valence and arousal ratings could be best described by a classical boomerang-shaped function. However, the content of the pictures (animals, faces, landscapes, objects, or people) had a significant effect on the ratings for valence and arousal. These findings indicate that further studies in cross-cultural affective research should control for the content of stimuli.